Evaluation of the mechanical behaviour of Telemark ski boots: Part I - materials characterization in use conditions - Natali, A. N.; Todros, S.; Venturato, C.; Fontanella, C. G. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
This study reports the first part of the analysis for the evaluation of the mechanical behaviour of ski boots by means of an integrated approach that considers polymeric materials characterization, in Part I, and numerical structural analysis, in Part II. In the present Part I, different techniques are adopted to characterize the mechanical behaviour of the polymeric materials used for ski boots, to define the elastic, visco-elastic, temperature and weathering-dependent characteristics. Experimental data provide fundamental information on mechanical response, in particular taking into account the effect of the environmental conditions, due to temperature variation, ultraviolet radiation and water absorption, which are correlated to the definition of reliability and durability of the materials. In more detail, experimental results from tensile tests and dynamic mechanical analysis are reported, evaluating mechanical response and chemical conformation of the polymers. Materials properties are correlated with the specific use conditions and boot structure, to be able to evaluate and preserve overall performances and general safety requirements of ski boots. This activity represents a reference procedure for the evaluation of the material mechanical behaviour that must be considered within the structural analysis.